2023
DOI: 10.1097/cnj.0000000000001017
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Caregiving Strategies, Quality of Life, and Stress Among Faith Community Nurses and Faith Leaders in Appalachia

Abstract: : Faith community nurses (FCNs), pastors, and priests faced many challenges from the COVID-19 pandemic, serving as frontline sources of support for congregants. The aim of this study was to identify the most common care strategies used during the COVID-19 pandemic and examine professional quality of life, perceived stress, and associated factors in faith leaders and FCNs in rural Appalachia. Using a cross-sectional, descriptive survey design, high compassion satisfaction was reported along with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…56 Families could also benefit from volunteer home care interventions such as faith-based nursing home visits. 57 Also, the positive evaluations of the telephone focus group interaction in this study indicated that such discussions might be used to combat caregiver loneliness. It is also important to ensure caregivers have access to national online or telephone information resources.…”
Section: Implications For Practicementioning
confidence: 74%
“…56 Families could also benefit from volunteer home care interventions such as faith-based nursing home visits. 57 Also, the positive evaluations of the telephone focus group interaction in this study indicated that such discussions might be used to combat caregiver loneliness. It is also important to ensure caregivers have access to national online or telephone information resources.…”
Section: Implications For Practicementioning
confidence: 74%
“…Also, enrolled participants identified other possible homes to visit. A key in recruitment was the guidance of the WVU School of Nursing Associate Dean for Community Engagement, based on her previous clinical care in rural areas and her county activities, such as her faith-based nursing program [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hebert and colleagues (2009) recommended that to better prepare family caregivers for palliative care, nurses must provide them with specific information tailored to their home care needs and continue communication for caregivers to seek and process the information. Also, integrating spiritual wellbeing support is a culturally appropriate intervention to help these patients and family caregivers in rural Appalachia manage health challenges (Mixer et al, 2023;Smothers et al, 2023).…”
Section: Implications For Nursing Practicementioning
confidence: 99%